Factors Affecting Collateral Valuation Performance During the Covid-19 Pandemic: An Evidence from Islamic Bank in Indonesia - Riansyah Rainal Purnama; Siti Jahroh; Moch. Hadi Santoso; Ahmad Rifai Ahmad Rifai (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2021)
This study aims to analyze the performance of collateral appraisers during the Covid-19 pandemic by using the variables of competence, motivation, and work stress as exogenous variables and through satisfaction as a mediating variable. Data for this study was collected through an online questionnaire from an Islamic bank in Indonesia. It involved 96 respondents, determined by the census sampling technique. Structural Equation Modeling with PLS version 3.0 was employed as an analysis tool. The results showed that competence, motivation, and satisfaction positively and significantly affected performance. In contrast, job stress had a negative and significant effect on the satisfaction and performance of collateral appraisers. The managerial implications that can be applied in the company are maintaining and increasing competence and motivation, increasing satisfaction, and quickly resolving sources of work stress.==========================================================================================================ABSTRAK – Faktor-Faktor yang Mempengaruhi Kinerja Penilai Agunan pada Masa Pandemi Covid-19: Kajian pada Bank Syariah di Indonesia. Penelitian ini bertujuan untuk menganalisis kinerja penilai agunan selama masa pandemi Covid 19 dengan menggunakan variabel kompetensi, motivasi dan stres kerja sebagai variabel eksogen dan variabel kepuasan sebagai variabel mediasi. Data penelitian diperoleh dari penyebaran kuesioner pada sebuah bank syariah di Indonesia. Responden penelitian ini berjumlah 96 orang yang didapat berdasarkan teknik census sampling. Analisis dilakukan dengan Structural Equation Modeling dengan PLS versi 3.0. Hasil penelitian menunjukkan bahwa kompetensi, motivasi dan kepuasan berpengaruh positif dan signifikan terhadap kinerja, sedangkan stres kerja berpengaruh negatif dan signifikan terhadap kepuasan dan kinerja agunan penilai. Implikasi manajerial yang dapat diterapkan di perusahaan adalah mempertahankan dan meningkatkan kompetensi dan motivasi, meningkatkan kepuasan, dan cepat menyelesaikan sumber stres kerja.